Is the association of overweight and obesity with colorectal cancer underestimated?: an umbrella review of systematic reviews and meta-analyses - Mandić, Marko; Li, Hengjing; Safizadeh, Fatemeh; Niedermaier, Tobias; Hoffmeister, Michael; Brenner, Hermann (European journal of epidemiology, 2023)
Although high body-mass index (BMI) is associated with increased risk of developing colorectal cancer (CRC), many CRC patients lose weight before diagnosis. BMI is often reported close to diagnosis, which may have led to underestimation or even reversal of direction of the BMI-CRC association. We aimed to assess if and to what extent potential bias from prediagnostic weight loss has been considered in available epidemiological evidence. We searched PubMed and Web of Science until May 2022 for systematic reviews and meta-analyses investigating the BMI-CRC association. Information on design aspects and results was extracted, including if and how the reviews handled prediagnostic weight loss as a potential source of bias. Additionally, we analyzed how individual cohort studies included in the latest systematic review handled the issue. Overall, 18 reviews were identified. None of them thoroughly considered or discussed prediagnostic weight loss as a potential source of bias. The majority (15/21) of cohorts included in the latest review did not exclude any initial years of follow-up from their main analysis. Although the majority of studies reported having conducted sensitivity analyses in which initial years of follow-up were excluded, results were reported very heterogeneously and mostly for additional exclusions of 1-2 years only. Where explicitly reported, effect estimates mostly increased with increasing length of exclusion. The impact of overweight and obesity on CRC risk may be larger than suggested by the existing epidemiological evidence.